2022
DOI: 10.1111/sifp.12203
|View full text |Cite
|
Sign up to set email alerts
|

Interrupted Access to and Use of Family Planning Among Youth in a Community‐Based Service in Zimbabwe During the First Year of the COVID‐19 Pandemic

Abstract: The COVID‐19 pandemic has had serious impacts on economic, social, and health systems, and fragile public health systems have become overburdened in many countries, exacerbating existing service delivery challenges. This study describes the impact of the COVID‐19 pandemic on family planning services within a community‐based integrated HIV and sexual and reproductive health intervention for youth aged 16–24 years being trialled in Zimbabwe (CHIEDZA). It examines the experiences of health providers and clients i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…Informants reported that in some clinics, GM was completely suspended to allow for prioritisation of other health services. Stockouts particularly affected immunisation and family planning services [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…Informants reported that in some clinics, GM was completely suspended to allow for prioritisation of other health services. Stockouts particularly affected immunisation and family planning services [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, existing health systems delivery problems in Africa compounded by the pandemic translated to substantial gaps in access to SRH services. In Zimbabwe, COVID-19 substantially disrupted access to HIV and SRH services, such as discontinuity of family planning services due to border lockdowns, restricted movements and limited youth-friendly contraceptive service options compared with before the pandemic in a community health programme for youths 13. Dyer et al 14 also reported that youths in Kenya faced challenges refilling their medications or keeping to their healthcare appointments, which was exacerbated by efforts that were outrightly against comprehensive SRH messages and SRH communication by policy-makers and decision-makers, religious organisations, and parents 15.…”
Section: Introductionmentioning
confidence: 99%
“…In Zimbabwe, COVID-19 substantially disrupted access to HIV and SRH services, such as discontinuity of family planning services due to border lockdowns, restricted movements and limited youth-friendly contraceptive service options compared with before the pandemic in a community health programme for youths. 13 Dyer et al 14 also reported that youths in Kenya faced challenges refilling their medications or keeping to their healthcare appointments, which was exacerbated by efforts that were outrightly against comprehensive SRH messages and SRH communication by policy-makers and decision-makers, religious organisations, and parents. 15 Even in South Africa, about 22.4% of adults could not access condoms during the first wave of the COVID-19 pandemic, 16 while utilisation of family planning services declined during the lockdown.…”
Section: Introductionmentioning
confidence: 99%